Hydrodynamic resistance prediction of an Olympic Class Sailing Dinghy using CFD and towing tank testing - Kemeth, F.; Hafenecker, S.; Jakab, S.; Varga, M.; Csielka, T.; Couronné, S. (Sports Science Research and Technology Support: Second International Congress, icSPORTS 2014, Rome, Italy, October 24-26, 2014, Revised Selected Papers, 2015)
The study presented in this paper aims at investigating, from a hydrodynamic point of view, the most favourable attitude of a sailing dinghy. The procedure includes both an experimental and a numerical approach. Of interest is if these two methods gives analogous results in terms of resistant force and optimal attitude. The numerical study extends to investigating the effects of adding appendages and leeway to the computational model. As this addition strongly affects the computational effort it is also of interest for future reference to see is the same attitude can be predicted this way and thus be discarded from future studies of this kind.